Canada 2026 - Sainsbury, Brendan; Bain, Jennifer (Cook); Balsam, Joel; Bierman, Jonny; Bujan, Bianca; Heller, Carolyn B.; Lockhart, Jessica Wynne; Noble, Isabella; Olsen, Debbie, 1965-; Rhyno, Darcy Keith; Woolsey, Barbara (Lonely Planet guidebooks., 2026)
Lonely Planet's Canada is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Savour culture in Quebec City, marvel at Niagara Falls, and hike in the Rockies; all with your trusted travel companion. Get to the heart of Canada and begin your journey now!